Summer camp critter jitters - John, Jory; Climo, Liz (Dial Books for Young Readers, 2021)
Animals have different anxieties about going off to summer camp.
A variety of animals with different anxieties about going off to summer camp receive reasurrance, in this story about going to a new place.
Ages 4-8.
Grades 2-3.
Keywords: Camps -- Fiction; Animals -- Fiction